Surgical treatment of bilateral atrophic mandible fracture in edentulous patients (Research, Society and Development, 2023)
Atrophic mandible fractures in edentulous patients constitute a subgroup of facial injuries that mostly affect geriatric individuals. Thus, the perioperative protocol of the elderly injured patient must be performed differently from young patients and, many times, they are more complex procedures. Thus, this article aims to review the characteristics, treatment options and complications of surgical treatment of bilateral fracture of the atrophic mandible in edentulous patients. For the construction of this article, a bibliographical survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, with the help of the Mendeley reference manager. Articles were covered between the years 2000 to 2023. Surgical treatment is still relatively preferred for atrophic edentulous mandibular fractures based on patient tolerance. Treatment of cases with mild atrophy is similar to that of general mandibular fractures. For cases with severe atrophy, an extraoral incision should be used for fixation and damage to the periosteum should be minimized to preserve the blood supply. The choice of bone plate is most indicated for maximum stability to minimize complications.